1996
DOI: 10.1183/09031936.96.09010007
|View full text |Cite
|
Sign up to set email alerts
|

Resection rates and postoperative mortality in 7,899 patients with lung cancer

Abstract: Postoperative death used to be an important complication of resections for lung cancer, especially in elderly patients. To support decision making in a general situation, contemporary results and prognostic factors were evaluated.The computer records of 7899 lung cancer patients, diagnosed from 1984 until 1992 in hospitals connected to the Rotterdam Cancer Registry, were analysed to evaluate resection rates and 30 day postoperative mortality.Resections were carried out in 20% of all patients. In patients 70 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
122
1
11

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(146 citation statements)
references
References 18 publications
12
122
1
11
Order By: Relevance
“…The estimated extent of lung resection in the present patients also entered the regression model as statistically significant, which is consistent with reports in the literature [3,22,23] and clinical expectancy. Its predictive value is yet to be confirmed by further studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The estimated extent of lung resection in the present patients also entered the regression model as statistically significant, which is consistent with reports in the literature [3,22,23] and clinical expectancy. Its predictive value is yet to be confirmed by further studies.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent representative survey [3] in 7,899 patients, a mortality rate of 8% for pneumonectomy and 3% after lesser resection was found in patients of >70 yrs of age, compared to an overall 1.4% mortality rate in patients of <60 yrs of age. Interestingly, age was not an independent predictor for postoperative complications in the present regression analysis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6,7 Studies with a large sex bias in referral for surgery present difficulties in interpretation, because it is unclear which selection factors led to this discrepancy. Our study eliminated this problem by analyzing a subset consisting of only the surgical services without a large sex bias in presentation for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an association has been found between males and an increase in postoperative mortality in pulmonary resection and hip replacement. [6][7][8] Males have also been associated with other adverse outcomes following noncardiovascular surgery, such as increased intensive care unit (ICU) admissions and rates of sepsis. 9 In a study of surgical ICU patients, males were shown to have a poorer prognosis compared with females.…”
Section: Résumémentioning
confidence: 99%